The need to transform HR activities in the digital economy (MMIT Proceedings, 2024)
This article examines the main trends and drivers driving changes in human resource management. Special attention is paid to the introduction of digital technologies such as artificial intelligence, big data, and process automation, which significantly change traditional approaches to recruitment, talent management, employee training and development.